THE SCHISTOSOMULA TEGUMENT ANTIGEN AS A POTENTIAL CANDIDATE FOR THE EARLY SEROLOGICAL DIAGNOSIS OF SCHISTOSOMIASIS MANSONI - Grenfell, Rafaella; Martins, Watson; Silva-Moraes, Vanessa; Araujo, Neusa; Oliveira, Edward; Fonseca, Cristina; Coelho, Paulo Marcos Zech (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
If Schistosoma mansoni infection could be detected in its early stages, especially before the egg deposition in the host tissues, the development of severe pathologic lesions could be efficiently prevented. We therefore developed an indirect enzyme-linked immunosorbent assay based on the detection of specific IgG against schistosomula antigens (ELISA-SmTeg). The assay was applied in sera samples from non-infected and infected mice collected seven and 15 days post-infection. The results were compared to the number of adult worms obtained by perfusion of the murine hepatic system 50 days post-infection. The sensitivity and specificity of the ELISA-SmTeg were 100% (p = 0.0032 and 0.0048 respectively for seven and 15 days of infection) with a cutoff value of 0.15 (p = 0.0002). Our findings show a novel low-cost serological assay using antigens which are easy to obtain, which was able to detect all the infected mice as early as seven days post-infection.